Factors Affecting the Participation Rate of Women in the Labor Force in Lima Puluh Kota Regency Using Probit Regression Analysis - Mutiya Zulfa; Helma (Rangkiang Mathematics Journal, 2024)
Labor currently plays a very important role in a country's economy. In the labour sector, women still experience discrimination, which causes the Labor Force Participation Rate (LFPR) of women to remain low compared to men. The LFPR of men in Kabupaten Lima Puluh Kota is higher than the LFPR of women. In 2022, the female LFPR was 63.75%, meaning that of the total labour force, around 63.75% of them were working or looking for work. This study aims to determine the factors that influence women's participation in the labour force in Kabupaten Lima Puluh Kota. This research is applied using the probit regression analysis method. The data used is secondary data, which is microdata from the National Labor Force Survey (SAKERNAS). Based on the results of the analysis, the factors that influence the level of women's participation in the labour force in Kabupaten Lima Puluh Kota in 2022 are education level, age, job training status, and status as head of household.